2019
DOI: 10.1186/s12935-019-0764-7
|View full text |Cite
|
Sign up to set email alerts
|

Roles of β-catenin, TCF-4, and survivin in nasopharyngeal carcinoma: correlation with clinicopathological features and prognostic significance

Abstract: Background Nasopharyngeal carcinoma (NPC) is a common malignant tumor of the head and neck region with poorly understood progression and prognosis. The present study aims at exploring whether the expression of β-catenin, TCF-4, and survivin affects clinicopathological features and prognostic significance in NPC. Methods We enrolled 164 patients with NPC and 70 patients with chronic nasopharyngitis (CNP) in this study. Reverse transcription quantitative polymerase chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Sensitivity analysis suggested that the results of EA-IgA levels and OS were influenced by data from Jin et al [ 17 ]. After the data from this article were removed, the heterogeneity reduced to I 2 < 50%.…”
Section: Resultsmentioning
confidence: 99%
“…Sensitivity analysis suggested that the results of EA-IgA levels and OS were influenced by data from Jin et al [ 17 ]. After the data from this article were removed, the heterogeneity reduced to I 2 < 50%.…”
Section: Resultsmentioning
confidence: 99%
“…β-catenin, a key component of the canonical Wnt signaling pathway, has been demonstrated to be upregulated in NPC patients, which was correlated with the patient’s survival. It has been elucidated as an independent prognostic factor [ 56 , 57 , 58 , 59 ] and is involved in the advanced stages of NPC [ 17 ]. β-catenin has been found to regulate oncogenes such as CYCLIN D1, PDK, MTC-1, MMP7, fibronectin, COX-2, AXIN-2, and C-MYC.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of OS included 8 studies [32,37,43,44,[47][48][49][50] with 910 patients. The heterogeneity test showed no significance (I 2 =2.5%; P=0.410); however, we found a significant association between survivin and OS.…”
Section: Survivin and Survivalmentioning
confidence: 99%